Environmental Enrichment During Adolescence Mitigates Cognitive Deficits and Alcohol Vulnerability due to Continuous and Intermittent Perinatal Alcohol Exposure in Adult Rats - Brancato, Anna; Castelli, Valentina; Lavanco, Gianluca; Cannizzaro, Carla (Frontiers in Behavioral Neuroscience, 2020)
Perinatal alcohol exposure affects ontogenic neurodevelopment causing physical and functional long‐term abnormalities, to which treatment strategies are limited. This study investigated long-term consequences of continuous and intermittent maternal alcohol drinking on behavioural readouts of cognitive function and alcohol vulnerability in the offspring. The effects of environmental enrichment during adolescence were also evaluated. Female rats underwent continuous (CAD) – or intermittent alcohol drinking paradigm (IAD), along pregestation, gestation and lactation periods - equivalent to the whole gestational period in humans. Male offspring were reared in standard conditions or environmental enrichment (EE) until adulthood and were then assessed for declarative memory in the novel object recognition test; spatial learning, cognitive flexibility and reference memory in the Morris water maze; alcohol consumption and relapse by a two-bottle choice paradigm. Our data show that perinatal-CAD decreased locomotor activity, exploratory behaviour and declarative memory with respect to controls; whereas perinatal-IAD displayed impaired declarative memory and spatial learning and memory. Unless both perinatal alcohol exposed offspring showed higher vulnerability to alcohol consummatory behaviour than controls, prenatal-IAD rats showed a relevant increase in alcohol consumption and relapse with respect to perinatal-CAD progeny. EE rescued declarative memory deficits in perinatal-CAD, while mitigated spatial learning and reference memory impairment in perinatal-IAD progeny. In addition, EE decreased vulnerability to alcohol in both control and perinatal alcohol exposed rats. Maternal alcohol consumption produces drinking pattern-related long-term consequences on cognition and vulnerability to alcohol in the offspring. However, adolescence provides a window of opportunity to increase positive environmental stimuli that curtail the detrimental effects of developmental alcohol exposure.